Relationships between the magnitude of representational momentum and the spatial and temporal anticipatory judgments of opponent’s kicks in taekwondo - Imanaka, Kuniyasu; Sugi, Takahiro; Nakamoto, Hiroki (Frontiers in Psychology, 2023)
For successful actions in a fast, dynamic environment such as sports, a quick successful anticipation of a forthcoming environmental state is essential. However, the perceptual mechanisms involved in successful anticipation are not fully understood. This study examined the relationships between the magnitude of representational momentum (RM) as a forward displacement of the memory representation of the final position of a moving object (which implies that observers perceptually "see" a near future forthcoming dynamic environmental state) and the temporal and spatial anticipatory judgments of the opponent's high or middle kicks in taekwondo. Twenty-seven participants (university taekwondo club members and nonmembers) observed video clips of taekwondo kicks that vanished at one of ten frame positions prior to the kick impact and performed three tasks consecutively: anticipatory coincidence timing (CT) with the arrival of kick impact, judgment of the kick type (high and middle kicks) by forced choice, and judgment of the vanishing frame position (measuring RM). Our results showed significant group effects for the number of correct kick-type judgments and the judgment threshold for kick-type choice (kick-typeJT), which was estimated in terms of individual psychometric function curves. A significant correlation was found between the magnitude of RM (estimated at kick-typeJT) and kick-typeJT, but not between the CT errors (estimated at kick-typeJT) and kick-typeJT. This indicates that the magnitude of RM may play an influential role in quick kick-type judgments, but not in coincidence timing while observing an opponent's kick motion. These findings suggest that subjective anticipatory perception or judgment of the future spatial state is vital to anticipatory actions under severe time constraints.